Cameron Pass, CO Spring 2019: Ground-penetrating radar surveys, snow depths, and snowpits - Bonnell, Randall; McGrath, Daniel (Colorado State University. Libraries, 2021)
This dataset contains snow depths, measurements from snowpits, ground-penetrating radar raw files, and derived liquid water content values collected at Cameron Pass, CO during Spring 2019. Snow depths were measured using a manual probe. Snowpit data includes density and temperature measurements, stratigraphy notes, and weather notes. Ground-penetrating radar was collected using a 1 GHz Sensors & Software ProEx unit coupled to the snow surface. Liquid water content was calculated using the picked two-way travel time from processed ground-penetrating radar, snow densities, and snow depths.
This dataset was collected to study the development of liquid water content along repeated transects using ground-penetrating radar during the spring of 2019. Data includes raw ground-penetrating radar files, snow depths, measurements from snowpits, and derived liquid water content. The data were collected over seven survey dates spanning 2019-04-05 to 2019-06-19 at Cameron Pass, Colorado.
Department of Geosciences
Keywords: snow water equivalent; snow survey; continental snowpack; wet snow; ground penetrating radar; snow remote sensing